Redesign of hard disk drive for increased productivity and scrap minimization using design for assembly and variation system analysis - Rachoti, Matamari (2011)
The hard disk drive industry is marked by intense competition and rapid technological change. Opportunities for cost reduction are eagerly sought after by the industry; designing for ease of assembly is one such avenue. Associated with assembly is dis-assembly, the pre-requisite to re-work, a significant cost driver in the disk drive industry. Another avenue is the dimensional